Microbiota modulates the steroid response to acute immune stress in male mice - Vagnerová, Karla; Gazárková, Taťána; Vodička, Martin; Ergang, Peter; Klusoňová, Petra; Hudcovic, Tomáš; Šrůtková, Dagmar; Petr Hermanová, Petra; Nováková, Lucie; Pácha, Jiří (Frontiers in Immunology, 2024)
Microbiota play a role in shaping the HPA-axis response to psychological stressors. To examine the role of microbiota in response to acute immune stressor, we stimulated the adaptive immune system by anti-CD3 antibody injection and investigated the expression of adrenal steroidogenic enzymes and profiling of plasma corticosteroids and their metabolites in specific pathogen-free (SPF) and germ-free (GF) mice. Using UHPLC-MS/MS, we showed that 4 hours after immune challenge the plasma levels of pregnenolone, progesterone, 11-deoxycorticosterone, corticosterone (CORT), 11-dehydroCORT and their 3-, 5-, and 20-reduced metabolites were increased in SPF mice, but in their GF counterparts, only CORT was increased. Neither immune stress nor microbiota changed the mRNA and protein levels of enzymes of adrenal steroidogenesis. In contrast, immune stress resulted in downregulated expression of steroidogenic genes (Star, Cyp11a1, Hsd3b1, Hsd3b6) and upregulated expression of genes of the 3-hydroxysteroid oxidoreductase pathway (Akr1c21, Dhrs9) in the testes of SPF mice. In the liver, immune stress downregulated the expression of genes encoding enzymes with 3-hydroxysteroid dehydrogenase (HSD) (Hsd3b2, Hsd3b3, Hsd3b4, Hsd3b5), 3-HSD (Akr1c14), 20-HSD (Akr1c6, Hsd17b1, Hsd17b2) and 5-reductase (Srd5a1) activities, except for Dhrs9, which was upregulated. In the colon, microbiota downregulated Cyp11a1 and modulated the response of Hsd11b1 and Hsd11b2 expression to immune stress. These data underline the role of microbiota in shaping the response to immune stressor. Microbiota modulates the stress-induced increase in C21 steroids, including those that are neuroactive that could play a role in alteration of HPA axis response to stress in GF animals.